4, 21‐Secovincanol, a Novel Immunosuppressive Monoterpenoid Indole Alkaloid from Kopsia Hainanensis. Issue 5 (30th March 2021) - Liu, Lu; He, Ting; Liu, Ya‐Ping; Cao, Jian‐Xin; Cheng, Gui‐Guang
Abstract: 4, 21‐Secovincanol (1 ), a novel C‐21/N‐4 cleavage monoterpenoid indole alkaloid, along with four analogs (2 –5 ), were obtained from the aerial parts of Kopsia hainanensis . Structurally, compound 1 might be a derivative of epivincanol (2 ) via C‐21/N‐4 cleavage. Their structures were confirmed by means of comprehensive spectroscopic data analysis and comparison with the reported data. All isolates significantly inhibited Con A‐stimulated mice splenocytes proliferation at 10–40 μM in a dose‐dependent manner in vitro . Especially, compound 3 exhibited potent activities comparable to positive control (Dexamethasone, DXM). Abstract :